STEM-Based Physics Learning: Enhancing Conceptual Understanding in 21st Century Education - Bahtiar; Ibrahim (Journal of Classroom Action Research, 2025)
This study aims to analyze the effectiveness of STEM-based learning in improving conceptual understanding of prospective physics teachers. The method used is quantitative with a one-group pretest-posttest design. This study involved 50 students as samples selected purposively. The research instrument consisted of 20 multiple-choice questions categorized based on cognitive levels C1 to C6. The data analysis technique in this research uses descriptive statistical analysis. Data obtained from the pretest and posttest results were analyzed by calculating the average value, standard deviation, and percentage increase in student understanding. The results showed that STEM-based learning improved conceptual understanding with an average increase of 23.10%, with a minimum score increasing from 30 to 60 and a maximum score from 80 to 90. Analysis based on cognitive levels showed the largest increase in C1 (26.0%) and the smallest in C2 (18.5%). These findings indicate that the STEM approach is effective in strengthening students' conceptual understanding and critical thinking skills. Therefore, STEM-based learning is recommended to be applied in science education to improve the quality of prospective teachers.